Design of A Soil Moisture and pH Monitoring System for Tomato Plants - Barki, Yori Saepul; Ramadhan, Teguh Ikhlas; Supriatman, Agus (Jurnal Prajaiswara, 2024)
In this era of globalization, many farmers are still less intensive in monitoring the growth period of their plants because tomato plants require an adaptation process to the environment and are very sensitive to soil moisture and soil pH. One of them is a Soil Humidity and pH Monitoring System to help farmers increase the harvest success rate of tomato plants. This monitoring system can provide quick information regarding soil moisture and pH conditions which can be monitored via gadget using the Telegram Bot. This soil control must have a pH of around 5-7 and humidity of around 60-80%. Detection of pH and humidity in soil using Soil Moisture and Soil pH sensors. This monitoring system is designed using Arduino Uno and NodeMCU as microcontrollers. With this pH and soil moisture monitoring system for tomato plants, soil conditions can be maintained and controlled easily because it can be done via Telegram Bot.